The Potential Anti-Cancer Effects Of Psidium Guajava (Guava) Leaves On Coloretal Cancer Via The Inhibition Of Angiogenesis - Bronwyn, Lok (2019)
Colorectal cancer, which is the cancer that develops in the colon or rectum, is one of the most common cancers that lead to death. The prevalence of colorectal cancer in Malaysia is expected to increase due to the aging population, socioeconomic advances, and increasingly Westernised diet and lifestyle. The growth of colorectal tumours beyond a certain size, as well as their metastatic spread, is dependent on the increase in angiogenesis of their surrounding vasculature. As Psidium guajava (guava) leaves are rich in phenolic compounds, flavonoids, carotenoids, and vitamins, the anti-angiogenic and anticancer activities of P. guajava leaf extracts were investigated to assess their potential in the treatment of the angiogenesis-dependent colorectal cancer. Three extracts were produced using distilled water, ethanol, and n-hexane as solvents, and were labelled as dH2O, EOH, and NH. The extracts were physically characterised through gas chromatography–mass spectrometry (GC-MS), ultraviolet-visible spectroscopy (UV-Vis), and Fourier transform infrared spectroscopy (FTIR). Through the DPPH radical scavenging, total phenolic content, and total flavonoid content assays, the EOH extract was found to have the highest antioxidant activity. The dH2O and EOH extracts exhibited more inhibitory activity against EA.hy926 (human vascular endothelial) cell viability and microvessel growth from rat aortic rings compared to the NH extract, indicating a better anti-angiogenic activity.